Agar Oil from the Wood of Aquilaria agallocha Roxb. - , Sadgopal; Varma, B. S. (Indian Forester, 1952)
A simple and economic method of distilling the essential oil of agar from the infected wood of Aquilaria agallocha Roxb. has been developed. The process can be worked as a profitable cottage scale industry. Details of the distillation plant and accessories as well as processing are indicated. Yield percentages of agar oil from various grades of wood and their physical constants have been recorded. Preparation of highly concentrated attars under the new technique has also been shown to yield better quality at lower cost. The paper incidentally summarises the present day knowledge regarding the factors responsible for the attack of sound agarwood by certain fungus and the consequent development of the agar oleoresin. Agar oil prepared by the new method has a true balsamic aroma with a woody back-note. Its high fixative value and exotic character will make an important addition to the list of Indian essential oils of great odour appeal.